Activity of the Immobilized Candida Rugosa Lipase - Singh, Kavya (My University, 2012)
In the present study Candida rugosa lipase has been immobilized on MCM- 41 support through sol – gel process. The immobilized enzyme was entrapped by the poly condensation of silica precursors namely tetramethoxyorthosilane /tetraethoxyorthosilane(TEOS) and iso-butyltrimethoxysilane (iso- BTMS). The immobilized enzyme was characterized by scanning electron microscopy, Fourier Transformed Infrared (FT–IR) and UV–Visible Spectrophotometer. Kinetic parameters viz., Michaelis-Menten constant (Km), Maximum rate of reaction (Vmax), Turnover number (kcat) and Specificity constant (kcat /Km) for immobilized Candida rugosa lipase were determined by using Michaelis-Menten and Lineweaver- Burk approach.
Master of Science (Chemistry)
Keywords: Immobilization, Lipase; Candida-Rugosa